The role of work engagement in achieving work-life balance in organic workers - Fitri, Risqika Lailati; Hurriyati, Dwi (Institut Agama Islam Negeri Langsa, 2024)
A high workload without being balanced with efforts to balance work life will lead to problems in the world of work. This study aims to determine the relationship between organic workers' work engagement and work-life balance. This research is a correlative quantitative study with the participants being organic workers at PT Pertamina Patra Niaga Regional Southern Sumatra, totaling 146 people. The sampling technique used in this study was simple random sampling. Data collection was done using Work-life Balance and Work Engagement Scales. This study uses simple linear regression test analysis techniques. The results showed a significant relationship between work engagement and work-life balance (r = .476, p < .01). Work engagement's practical contribution to work-life balance is 22.7%, and other factors influence the remaining 77.3%.